Preventive Environmental Administrative Control Mechanisms and Administrative Penalties for Violating them - Boudeffa, Ali; Tairi, Salah (Journal of Legal Studies and Researches, 2023)
The Algerian legislator hastened to develop legal and administrative means to protect the environment, and as long as the protection of the environment is one of the requirements of preserving public order, the administration resorts to imposing restrictions on the freedoms and rights of individuals, using the means of environmental administrative control, whether they are preventive mechanisms or administrative penalties.